STUDI KOMPARATIF ANGKUTAN BARANG MENGGUNAKAN MODA LAUT DAN DARAT DI PULAU JAWA - Mohd Ridwan (TEKNIK, 2011)
A comparative study of the use of marine and land modes of transportation of goods, aiming to get the value ofgoods transport which is more economical, especially in Java. The output from this study can be used asstepping and the consideration for the government in planning the transport infrastructure of goods and assistemployers to make decisions in order to utilize the mode of transport of goods/ containers that will be marketed.There are many modes of transport that can be utilized in the transportation of goods, namely land modes:Railway containers, trucks/ trailer containers, marine modes: container ship, barge and container ship, RoRocontainer and trailer / truck, so it is necessary for technical and economic studies to assess the transport ofgoods by means of which one is more economical.The results of this study, is the most economical freight rate is the mode of sea transportation of container bargethat only Rp. 13,028,845.93 / TEU (Rp. 651,4/kg).